Proust as Translator of Ruskin - Waldinger, Albert (Meta, 2009)
AbstractThis article deals with the committment of Proust to Ruskin as the moral authority of his time and, consequently, as a main influence on his own original work through the apprenticeship of translation. It examines these renderings (La Bible d’Amiens and Sesame et les lys) as transformations of allegory into symbol, foreshadowing his early Du côté de chez Swann and his final Le temps retrouvé) with the conclusion that Proust managed to realize the unity of abstract and concrete. Allegory, a Proustian “rhetorical trope” on the Cathedral of Amiens (according to De Man) and the Victorian public building, is such an abstraction opposite the concreteness and privacy of symbolism, the reality behind the trope as realized behind the styles of both Ruskin and Proust.